DINAMIKA KESENIAN TARI GANDRUNG DI AFDELING BANYUWANGI TAHUN 1890-1930 - Sauri, Sofyan (Historia, 2023)
This research is the dynamics of the Gandrung dance in Afdeling Banyuwangi from 1890-1930. The problem statement in this research is 1. How did the Gandrung Banyuwangi dance appear? 2. How was the condition of the Gandrung Banyuwangi dance in 1890-1930? 3. What influenced the Gandrung dance influence for the Banyuwangi people in 1890-1930 ?The method of this study used the historical method consisting of: heuristic, criticism, interpretation, and historiography. The approach used is a socio-cultural one. The analytical tools to obtain the substance needed in the research consist of Homi K Bhabha’s theory of hybridity and Edward W. Said’s theory of orientalism. The resultsshowed there was a change in the art of the Gandrung dance in Afdeling Banyuwangi from 1890-1930. These changes consist of: changes in the function of Gandrung dance from ritual dance to profane dance in performing arts, a change in costumes that significantly converges to the aesthetics of the Gandrung dancer's costume based on the manifestation of the resulting attractiveness, and a change in the musical instruments of the Gandrung dance art orchestra from simple become more complex. Incidentally, the art of the Gandrung dance creates an economic impact on the Gandrung dance artists and society. Politically, the identity bias of the Gandrung Banyuwangi dance is distorted by the profanity of the Gandrung dance from Banyuwangi. Gandrung Poem became a medium for the struggle of Banyuwangi artists to fight Dutch colonialism by using resistance reporting through “gending podo nonton”. The fading of the traditional grip on the Gandrung dance has made this art able to exist in the realm of art. Keywords: Afdeling Banyuwangi; Dutch Colonialism; Gandrung Dance; Identity Bias; Profanism